Examining the Work Engagement-Organizational Citizenship Behavior Link: The Moderating Role of Employee Personality - Krishnan, Ramesh; Muthusamy, Geetha; Loon, Koe Wei; Alias, Nurul Ezaili; Romaiha, Noor Rafhati; Kanchymalay, Kasturi (Information Management and Business Review, 2023)
Although previous researchers have paid significant attention to the effect of employee work engagement on employee involvement in organizational citizenship behavior (OCB), only a few have specifically examined the joint effects of employee work engagement and employee personality on employee involvement in OCB. Drawing upon the Social Exchange Theory, this study specifically examined the role of employee personality (agreeableness) as a moderator in the work engagement-OCB relationship. A total of 646 employees from three public healthcare institutions in Malaysia participated in this study. Moderated hierarchical regression results indicated a positive effect of work engagement with OCB and a significant interaction between work engagement and agreeableness personality in predicting OCB. However, the effect of work engagement on OCB was stronger for those respondents low in agreeableness than for those high in agreeableness personality, contrary to the hypothesis. Managerial implications and directions for future research are discussed.